2003
DOI: 10.1002/hlca.200390202
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylidene Carbenes. Part 32

Abstract: Dedicated to the memory of Jorge F. Lo¬pez-Herrera Acylation and sulfonylation of the N,N'-unsubstituted glucosylidenespirodiaziridines 1A/1B 95 : 5 with Ac 2 O, BzCl, FmocCl, TsCl, (naphthalen-2-yl)sulfonyl, and (2,4,6-triisopropylphenyl)sulfonyl chloride, and concomitant rearrangement gave the acylated and sulfonylated gluconolactone hydrazones 2B ± 2G in 40 ± 83% yield (Scheme 2). Similarly, the galacto and manno analogues 3A/3B 95 : 5 and 5A/5B 55 : 45 and the mannofuransoylidene-diaziridine 30 were acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Although some glycono-1,5-lactone tosylhydrazones are known in the literature [13][14][15], no analogous derivatives of 2-acetamido-2-deoxy-D-glucono-1,5-lactone could be found. Therefore, the synthesis of the planned inhibitors (Table 2) was based on our previous work [12] encompassing the synthesis of 2-acetamido-2-deoxy-D-glucono-1,5-lactone semicarbazones.…”
Section: Synthesis Of Inhibitorsmentioning
confidence: 99%
“…Although some glycono-1,5-lactone tosylhydrazones are known in the literature [13][14][15], no analogous derivatives of 2-acetamido-2-deoxy-D-glucono-1,5-lactone could be found. Therefore, the synthesis of the planned inhibitors (Table 2) was based on our previous work [12] encompassing the synthesis of 2-acetamido-2-deoxy-D-glucono-1,5-lactone semicarbazones.…”
Section: Synthesis Of Inhibitorsmentioning
confidence: 99%
“…Because of the instability of diazirines, they then employed the anomeric N ‐tosylhydrazone donors, which are benchtop stable carbene precursors. The sodium salts of these N ‐tosylhydrazones under photochemical conditions generate the corresponding anomeric carbenes, which undergo an O−H insertion reaction with alcohols to form O ‐glycosides (Scheme 1a) [13c] . A similar anomeric carbene has also been employed in protecting group‐free phosphorylations [14] .…”
Section: Introductionmentioning
confidence: 99%
“…From the 60s, various substituted diaziridines and diazirines were synthesized [29–43]. Halogen derivatives are ideal precursors for spectroscopic studies of carbens [44–46]; several derivatives were suggested as alkylating agents [47] and potential reagents for photolabeling of biological receptor sites [48–57], some of the substituted diaziridines and diazirines were investigated as anticancer drugs [58, 59], potential monoamine oxidase inhibitors [60, 61] and anesthetics [62, 63].…”
Section: Introductionmentioning
confidence: 99%